Coach learning and coach education: Portuguese expert coaches` perspective - Mesquita, I.; Ribeiro, J.; Santos, S.; Morgan, K. (The Sport Psychologist, 2014)
The aim of this study was to analyze Portuguese expert coaches` conceptions of learning sources that promote long-term coach development and the extent to which these sources are currently present in coach education programs. Six expert coaches were individually interviewed, using a semistructured format and the inter- views were analyzed using QSR N6 Nudist software. The results highlighted the participants` awareness of the uniqueness of coach education, emphasizing the importance of reflecting and engaging with a variety of learning experiences. Findings also revealed dissatisfaction with the current dominant education framework in Portugal, which remains excessively didactic and classroom-orientated. In contrast, the participants external- ized a constructivist approach for coach education assuming the need for theoretical knowledge to be framed in practical contexts, where they have the opportunity to share and reflect their own and others` experiences to develop learning. Such a position echoes Sfard`s acquisition and participation learning metaphors.